Real-World Verbal Communication Performance of Children Provided With Cochlear Implants or Hearing Aids. Issue 6 (July 2015) - Meister, Hartmut; Keilmann, Annerose; Leonhard, Katharina; Streicher, Barbara; Müller, Linda; Lang-Roth, Ruth
<x xml:space="preserve">Abstract</x> Objective To compare the real-world verbal communication performance of children provided with cochlear implants (CIs) with their peers with hearing aids (HAs). Study Design Cross-sectional study in university tertiary referral centers and at hearing aid dispensers. Methods Verbal communication performance was assessed by the Functioning after Pediatric Cochlear Implantation (FAPCI) instrument. The FAPCI was administered to 38 parents of children using CIs and 62 parents of children with HAs. According to the WHO classification, children with HAs were categorized into three groups (mild–moderate–severe hearing loss). Analysis of variance (ANOVA) was performed on the FAPCI scores, with study group, hearing age (i.e., device experience), and age at hearing intervention as sources of variation. Results ANOVA showed that hearing age and study group significantly contribute to the FAPCI outcome. In all study groups except the children with mild hearing loss, FAPCI scores increased alongside growing experience with the devices. Children with mild hearing loss using HAs showed higher scores than those with severe hearing loss or implanted children. There were no significant differences between the children with CIs and the children with moderate or severe hearing loss using HAs. Conclusion Real-world verbal communication abilities of children with CIs are similar to those of children with moderate-to-severe hearing loss using amplification. Because hearing age significantly influences performance, children with moderate-to-severe hearing loss using HAs and implanted children catch up with children with mild hearing loss at a hearing age of approximately 3 years.